Histopathological investigation of the effects of a combination of parenteral nutrition and hunger on rabbit splenic tissue (Annals of Medical Research, 2021)
Aim: Parenteral nutrition (PN) is a life-saving practice when the use of the gastrointestinal tract is not possible. However, PN can cause a variety of complications despite its many benefits. In this study, we examined the histopathological effects of PN combined with hunger in the splenic tissue of rabbits.Materials and Methods: The rabbits were divided into four groups. The hunger + PN (PNH) group was completely starved and received the daily energy requirement with PN via an intravenous central catheter. The second group received enteral nutrition + PN (PNEN), wherein half of the required daily calories were provided through enteral nutrition, and the other half, through PN. A third group comprised semi-hungry (SH) rabbits that were provided only half the required daily calories by oral feeding.They did not receive PN. The last group was the control group. After 10 days, the rabbits were euthanized, and splenic tissue samples were collected from all the groups and examined histopathologically.Results: The histopathological examination for the PNH group revealed damage in the form of germinal center effacement, reduction of white pulp, congestion of red pulp, and decreased cellularity in the periarteriolar lymphoid sheath. Immunohistochemical examination revealed a significant increase in the apoptotic activity of the splenic tissues of this group. The corresponding findings were mild in the PNEN group, and no signs of damage were found in the other two groups.Conclusion: PN combined with hunger appears to cause damaging effects on splenic tissue in rabbits. Adding enteral nutrition to PN may reduce these effects.